Connections Between Language and Mathematics in the Elementary Classroom - Roxanne Olsen (Canadian Journal for New Scholars in Education)
Mathematical literacy, also defined as numeracy, enables learners to connect their mathematical skills to real-world applications. Success in numeracy requires learners to be proficient with literacy skills and background knowledge to develop and implement their understanding. Language in mathematics can present a challenge to all students, in particular for those who are learning English as an additional language. This literature review includes peer-reviewed studies which examine language in mathematics, vocabulary development for mathematical understanding, and dialogue to support student learning. Educators can implement strategies to strengthen numeracy for all students, including those learning English as an additional language. Further research is needed to explore the complexities of problem-solving, transfer of reading skills into mathematics, and student assessment tools to allow educators to understand where learners will benefit from targeted support.